The Effect Beauty Vlogger And Lifestyle On Cosmetic Purchase Decision On E-Commerce Shopee (Survey Of University Of Perjuangan Tasikmalaya Female Students) - Ayu Sri Wandini; Askolani Askolani; Depy Muhamad Pauzy (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of Beauty Vlogger and Lifestyle on Cosmetic Purchasing Decisions at E-Commerce Shopee. This study uses a survey method with a causality research design. The type of data used is primary data and secondary data, with a sample of 100 respondents from students of the University of Perjuangan Tasikmalaya and using a purposive sampling method. The data analysis tool used is path analysis. The results of the study show that Beauty Vlogger has a positive and significant effect on the lifestyle of female students at the University of Perjuangan, Tasikmalaya. Beauty Vlogger has a positive and significant effect on cosmetic buying decisions on Shopee e-commerce. Lifestyle has a positive and significant effect on cosmetic purchasing decisions on e-commerce Shopee. Beauty Vlogger has a positive and significant effect on cosmetic purchasing decisions on e-commerce Shopee through Lifestyle for Students at the University of Perjuangan, Tasikmalaya.